RISKS IN THE MATTER OF PUBLIC PROCUREMENT FROM THE PERSPECTIVE OF LEGAL TREATMENT - BOGDAN, Anca Mădălina; BOGDAN, Adrian; RIZA, Ionuț (International Journal of Legal and Social Order, 2022)
Through this article, we aim to highlight the way in which managers from several public institutions in Romania perceive the risks regarding public procurement procedures from the perspective of the legal framework. The public procurement process represents a sequence of stages, following which the product or the right to use it, the service or the work is obtained, as a result of the award of a public procurement contract. The identification of errors/omissions that may occur during the realization of the public procurement process is an essential activity in order to analyze the results obtained in comparison with those expected in the planning stage and to be able to ensure the necessary conditions for the continuous improvement of the entire process. The control mechanism of the public procurement process must be based on specific risk analysis.